Exploring the Impact of Board Composition, Ownership Structure and Dividend Policy on IDX80 Companies: A Study of the Indonesian Stock Exchange - Prawestri, Adhelia Desi; Nurariska , Novita (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This study examines the influence of board composition (board size and frequency of board meetings) and ownership structure (state, institutional, managerial, family, and foreign ownership) on dividend policy. The independent variables include board size, frequency of board meetings, and various ownership structures, while the dependent variable is dividend policy. The sample comprises companies listed on the IDX80 index of the Indonesia Stock Exchange from 2019 to 2022. Using unbalanced panel data, the analysis spans four years and includes 117 companies. The data is secondary, sourced from the annual reports of these companies. Logistic regression analysis, conducted using Eviews 10, was applied to test the hypotheses. The findings reveal that board size has a positive impact on dividend policy, whereas the frequency of board meetings, state ownership, institutional ownership, managerial ownership, family ownership, and foreign ownership do not significantly affect dividend policy